Design Analysis of Sesame Spraying Machine for Burger Bun Production: Analisis Desain Mesin Penyemprot Biji Wijen untuk Produksi Roti Burger - Bayu Kusuma Atmaja; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background The increasing consumption of fast food has driven the need for efficient food production technologies, particularly in burger manufacturing. Specific Background Burger buns require uniform application of sesame seeds and liquid coating to maintain product quality and consistency. Knowledge Gap Conventional manual methods and existing machines still face limitations in efficiency, uniformity, and material usage optimization. Aims This study aims to design and analyze a sesame sprinkling and spray machine using two different conceptual models to improve production performance. Results The design process utilized SolidWorks simulation, showing that concept A produced a maximum von Mises stress of 38.10, while concept B reached 38.71. The safety factors were 4.46 and 4.39, respectively, indicating both designs are structurally safe. Concept B demonstrated better performance in terms of cost efficiency and more uniform sesame distribution due to its oscillating sieve mechanism. Novelty The study introduces a comparative design approach combining spraying and sprinkling mechanisms with improved uniformity through an eccentric motion system. Implications The findings provide practical insights for developing more efficient and cost-effective machinery in small to medium-scale burger production industries. Keywords: Burger Buns, Machine Design, Sesame Sprinkling, Spray System, SolidWorks Simulation Key Findings Highlights Concept B shows superior cost efficiency and distribution uniformity Both models meet safety standards based on structural simulation Oscillating sieve mechanism improves sesame application consistency me Spraying Machine for Burger Bun Production